Supervised mineral exploration targeting and the challenges with the selection of deposit and non-deposit sites thereof - Rahimi, Hossain; Abedi, Maysam; Yousefi, Mahyar; Bahroudi, Abbas; Elyasi, Gholam-Reza (Applied geochemistry, 2021)
Selection of non-deposit sites is a challenging issue affecting the application of supervised algorithms for modeling mineral exploration targets. For this, equal number of deposit and non-deposit sites has been widely applied for training purposes. In this paper, we investigated the effect of changes in the number of non-deposit sites on the effectiveness of exploration targeting models while the number of deposit sites is constant. The results obtained demonstrated that exploration targeting models are affected by the ratio of non-deposit and deposit sites. Thus, balancing between the number of deposit and non-deposit sites is an efficient way to produce more-reliable exploration targets when supervised algorithms are applied for modeling. The idea of this research came from the fact that mineralization is a rare event, and therefore, in a region of interest number of non-deposit sites is much more than that of deposit events. To illustrate the procedure proposed, we used an exploration dataset of porphyry Cu mineralization in Chahargonbad area, SE Iran. A sequence application of self-organizing map and multilayer perceptron neural network algorithm was applied to better illustration of the changing effects of the number of non-deposit sites on the ensuing exploration targeting models. •Counting of deposit and non-deposit sites is discussed for training purpose.•The number affects the ensuing exploration targeting models.•Making a balance between the two types of training data yields significant results.•Self-organizing map clustering approach leads to define non-deposit sites.